Analysis and assessment of life-cycle carbon emissions of space frame structures. (20th January 2023) - Xu, Xian; You, Jianzhou; Wang, Yafeng; Luo, Yaozhi
Abstract: The construction industry takes up a significant part of global energy consumption and carbon emissions, and thus accurate calculation and evaluation of full life-cycle energy consumption and carbon emissions of different types of building structures are important for low carbon-oriented structural design. Large-span structures usually consume more materials, need more complex construction processes, and thus have a larger environmental impact. In this study, the life cycle assessment of the carbon emission of space frame structures which is a classical type of large-span structure is conducted. Space frame structures with bolted spherical joints and space frame structures with welded hollow spherical joints are considered. The life cycle of a space frame structure is divided into four phases including component production, construction, maintenance, and demolition. The tiered hybrid method that combines process-based calculation and input-output analysis is adopted to evaluate the carbon emission of space frame structures. Parametrical studies on the height-span ratio and grid number are carried out using the proposed assessment scheme. The carbon emissions of the space frame structures with different types of joints are investigated and compared. It is found that lower material consumption does not always result in lower carbon emission, and thus it is necessary to evaluate the life-cycle carbon emission during lower carbon-oriented design of space frame structures. An equation for approximately and quickly estimating the carbon emission of space frame structures is fitted from the material consumption to carbon emission datum obtained from the parametrical studies. This study provides a useful reference for the carbon emission assessment and low-carbon oriented design of space frame structures. Highlights: A comprehensive analysis and assessment of life-cycle carbon emissions of steel grid structures is provided. The system boundary for the LCA of steel grid structures has been refined. The carbon emission factors for the production of steel grid structures are collected and compiled. An equation for approximately and quickly estimating the carbon emissions of steel grid structures is fitted and given.